1995
DOI: 10.1002/aic.690410706
|View full text |Cite
|
Sign up to set email alerts
|

Origin of disturbances in cocurrent gas‐liquid packed bed flows

Abstract: Visual, video, pressure, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…Moreover, flow hysteresis, another undesirable flow phenomenon, caused by flow maldistribution in parallel channels in a TBR, is highly influenced by initial start-up conditions and tends to abate after the entire bed is fully wetted. However, the underlying mechanism is not clearly understood and flow hysteresis cannot be well interpreted from macro-scale analyses (Krieg, Helwick, Dillon, & McCready, 1995;Lin, Juang, Chen, & Chen, 2001;Urseanu, Boelhouwer, Bosmanand, & Schroijen, 2004). Therefore, attempts have been made to understand detailed flow behavior inside the flow channels between catalyst particles.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, flow hysteresis, another undesirable flow phenomenon, caused by flow maldistribution in parallel channels in a TBR, is highly influenced by initial start-up conditions and tends to abate after the entire bed is fully wetted. However, the underlying mechanism is not clearly understood and flow hysteresis cannot be well interpreted from macro-scale analyses (Krieg, Helwick, Dillon, & McCready, 1995;Lin, Juang, Chen, & Chen, 2001;Urseanu, Boelhouwer, Bosmanand, & Schroijen, 2004). Therefore, attempts have been made to understand detailed flow behavior inside the flow channels between catalyst particles.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the trickle-bed reactor (TBR), in which gas and liquid reactants flow cocurrently downwards across packed solid catalyst beds, now represents an important class of multiphase reactors. The flow regime transitions in a fixed bed were traditionally investigated by experimental methods like nonlinear time analysis [13] and wall pressure fluctuations [14,15]. The multiphase flow in a fixed bed is extremely complex [5]; different flow patterns can be found, such as the gas-continuous or trickle flow at low liquid and gas rates, pulse flow at intermediate liquid and gas rates, and liquid continuous or dispersed bubble flow at higher liquid flow rates.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of pulse frequencies seems possible even if those, which correspond to low saturation values, are disregarded. Krieg et al(1995) also observed that moving pulses of relatively high hold up are present in trickle-fl ow at liquid velocities well below those associated with the transition to pulsing fl ow.…”
Section: Trickling To Pulsing Flow Transition Through Periodic Flow Fmentioning
confidence: 83%
“…Two-dimensional systems have been examined by Scriven and his students Melli et al, 1990). McCready and co-workers (Helwick et al, 1990;Krieg et al, 1995) offer an alternate approach and have examined experimentally predictions from stability analysis.…”
Section: Trickling To Pulsing Flow Transition Through Periodic Flow Fmentioning
confidence: 99%